Community-based Strategies for Optimising Mangrove Forest Tourism Management in Balang Baru Village, Jeneponto Regency - Rahim Sila, Sri Arfiani; Yayank, Andi Ridha; Molo, Hasanuddin (Jurnal Wasian, 2025)
Although SWOT analysis has been widely used for tourism and conservation planning, its application here highlights the institutional and social dynamics shaping mangrove ecotourism in a rural Indonesian context. The study reframes SWOT not merely as a planning tool but as a policy instrument to show how local collaboration, governance capacity and ecological rehabilitation can be aligned to sustain mangrove-based livelihoods. Grounded in the context of Balang Baru Village, where mangrove resources managed as a tourism area face increasing pressure from population growth and economic needs, this study aims to optimise the utilisation of the mangrove forest tourism area through the formulation of effective management strategies. Primary data were obtained from interviews with 15 respondents, including local residents, village government representatives, and members of the mangrove management group. The results identified ten strategic actions to strengthen mangrove tourism management, including the use of non-tourism zones for rehabilitation, the development of mangrove education parks, the establishment of an official tourism website, the improvement of facilities and infrastructure, and the enhancement of stakeholder collaboration. These strategies are expected to support sustainable mangrove management while improving community welfare through ecotourism development.